O estagiário da licenciatura ao estar com o professor regente que assume a modelagem matemática em sala de aula - Pereira, Emanueli (2023)
Research in Mathematical Modeling in Mathematics Education (MM) has numerous fronts and relevant themes. Preservice Training Teachers and Continues Learning are among the most important ones. In the context of Preservice Training, there is a large number of investigations that focus on student practices and a rather few studies in the context of supervised internships. However, from our literature survey, we found no research focused on the intern performing an internship with a regent teacher who has experience with (MM). This finding articulated with the interest in understanding the Preservice Training Teachers in (MM), which belongs to our comprehensive horizon, led to the establishment of the following research question: what is it, the lived experience of the intern of the Degree in Mathematics in the supervised internship with regent teachers who assume Mathematical Modeling in the classroom? Pursuing it from a phenomenological perspective, the need to understand the survey region was imposed, as well as to organize the thesis in a multipaper format. Three major aspects were investigated, which give the research a sense of totality: 1) the practices and actions of the subjects involved in the Supervised Internship in Mathematics in the State of Paraná; 2) The supervised internship within the scope of research in Mathematical Modeling in the Brazilian context. 3) The subject who experiences the supervised internship with the head teacher of the school who assumes Modeling in the classroom. These aspects led to the production of three articles, with two of them being about the qualitative meta-analyses and one focused on the significant subjects. The first work titled “Supervised Internship Practices of the Licentiate Degree in Mathematics in the State of Paraná”, revealed the actions and the way in which subjects are seen in this context. The second publication, “Mathematical Modeling and Supervised Curricular Internship: a focus on the literature”, revealed ways in which the internship has already been focused on in the community. The third and final text “The lived experience of the intern of the Licentiate Degree in Mathematics with a regent teacher who assumes Mathematical Modeling in the classroom”, includes aspects not yet discussed in the literature by analyzing the report of three significant subjects, two trainees and a new graduate. In every article, the aspects inherent to the questioned subject were studied, such as Preservice Training Teacher, supervised training and Mathematical Modeling. The experience lived by the subjects has favored different ways of approaching Modeling and practice in the classroom. It has also highlighted an open door to supervised internship theoretical, practical and reflective realization, recognizing the regent teacher as a trainer who shares the same values in educational terms.